Isolation and Contact Tracing Can Tip the Scale to Containment of COVID-19 in Populations With Social Distancing - Kretzschmar, Mirjam E.; Rozhnova, Ganna; van Boven, Michiel (Frontiers in Physics, 2021)
Novel coronavirus (SARS-CoV-2) has established itself in all parts of the world, and many countries have implemented social distancing as a measure to prevent overburdening of health care systems. Here we evaluate whether and under which conditions containment of SARS-CoV-2 is possible by isolation and contact tracing in settings with various levels of social distancing. To this end we use a branching process model in which every person generates novel infections according to a probability distribution that is affected by the incubation period distribution, distribution of the latent period, and infectivity. The model distinguishes between close contacts (e.g., within a household) and other contacts. Social distancing may affect the numbers of close and casual contacts differently, for example when household contacts remain unchanged while work and school contacts are reduced. The model allows explicit calculation of basic and effective reproduction numbers, and of exponential growth rates and doubling times. Our findings indicate that if the proportion of asymptomatic infections in the model is larger than 30%, contact tracing and isolation cannot achieve containment for a basic reproduction number R0 of 2.5. Achieving containment by social distancing requires a reduction of numbers of non-household contacts by around 90%. If containment is not possible, at least a reduction of epidemic growth rate and an increase in doubling time may be possible. We show for various parameter combinations how growth rates can be reduced and doubling times increased by contact tracing. Depending on the realized level of contact reduction, tracing and isolation of only household contacts, or of household and non-household contacts are necessary to reduce the effective reproduction number to below 1. In a situation with social distancing, contact tracing can act synergistically to tip the scale towards containment, and can therefore be a tool for controlling COVID-19 epidemics as part of an exit strategy from current lock-down measures or for preventing secondary waves.